INOVASI PEMBELAJARAN BERBASIS BOARD GAME UNTUK MENINGKATKAN KETERLIBATAN SISWA DI KELAS IV SEKOLAH DASAR (Sindoro: Cendikia Pendidikan, 2025)
Interactive and enjoyable learning has been proven to increase student engagement in the teaching and learning process. This article discusses the use of board games as a learning medium to teach the value of mutual cooperation in Civic Education (PKn) lessons. This learning medium is designed by integrating engaging game elements with educational content, enabling students to learn actively and participatively. Based on research findings, the use of board games has proven effective in creating a conducive and positive learning environment, enhancing students' understanding of the material, and contributing to the holistic development of their character.